1999
DOI: 10.1103/physrevb.59.13973
|View full text |Cite
|
Sign up to set email alerts
|

55MnNQR/NMR studies of the magnetic properties ofYMn2under pressure

Abstract: We report magnetic properties of the antiferromagnet YMn 2 as functions of pressure and temperature ͑T͒ obtained from the 55 Mn spin-lattice relaxation rate and the Knight shift. An energy-band narrowing due to electron correlation is indicated by the Knight shift measurement and the application of pressure is found to enhance the conduction electron bandwidth. In the pressure-induced paramagnetic state, the system undergoes a crossover from an itinerant spin fluctuation ͑SF͒ regime at low T to a local SF regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…6,22 However, this value is comparable to the value of YMn 2 in the paramagnetic state. 23,24 Below ϳ50 K, the plots deviate markedly from the straight lines and seem to come on other lines with different slopes. This phenomenon may be related to a marked upturn of the susceptibility on further cooling, and hence to a certain evolution of the electronic state suggested, for example, by muon spin relaxation measurements.…”
Section: ͑35͒mentioning
confidence: 93%
“…6,22 However, this value is comparable to the value of YMn 2 in the paramagnetic state. 23,24 Below ϳ50 K, the plots deviate markedly from the straight lines and seem to come on other lines with different slopes. This phenomenon may be related to a marked upturn of the susceptibility on further cooling, and hence to a certain evolution of the electronic state suggested, for example, by muon spin relaxation measurements.…”
Section: ͑35͒mentioning
confidence: 93%
“…In particular, a strong hyperfine field exerted on 55 Mn nuclei [corresponding to δ µ / √ 2 ≃ 1.2 GHz/µ B in Eq. ( 13)] drives the sensitive range of NMR up to such high frequencies 22 . Interestingly, the latest INS study of a singlecrystalline sample (x = 0.03) revealed that the intensity centered at approximately Q 0 = (1.25, 1.25, 0) (in reciprocal lattice units) exhibits anisotropic broadening along the Brillouin zone boundary, which is interpreted to be due to the degeneracy of states associated with geometrical frustration 24 .…”
Section: A Y(sc)mnmentioning
confidence: 99%
“…These spectra were analyzed by curve fitting using Eq. (22), where β = 1 and a p was replaced with A b as the time-independent background mainly originating from muons stopped in the sample holder. The signal-to-background ratio (A 0 /A b ) was ∼3.8 for the 4 He cryostat and ∼3 for the 3 He cryostat over a time range of 0-20 µs, allowing the reliable deduction of λ at small values (∼ 10 −2 µs −1 ).…”
Section: B Ymn 2 Zn 20−x In Xmentioning
confidence: 99%